2020
DOI: 10.3390/act9040132
|View full text |Cite
|
Sign up to set email alerts
|

Fault Estimation and Fault-Tolerant Control for the Pump-Controlled Electrohydraulic System

Abstract: This paper proposes a fault estimation and fault-tolerant control strategy with two observers for a pump-controlled electro-hydraulic system (PCEHS) under the presence of internal leakage faults and an external loading force. The mathematical model of the PCEHS is dedicatedly derived in the state-space form for developing control methodology. Two different observers are developed in which an extended state observer is applied to estimate the internal leakage flow rate, and a disturbance observer is used to dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Based on References [ 34 , 35 , 36 ], the proposed control strategy is ultimately uniformly bounded in the presence of matched and mismatched disturbances. The tracking errors and estimation errors of disturbances are bounded.…”
Section: Control Algorithm Designmentioning
confidence: 99%
“…Based on References [ 34 , 35 , 36 ], the proposed control strategy is ultimately uniformly bounded in the presence of matched and mismatched disturbances. The tracking errors and estimation errors of disturbances are bounded.…”
Section: Control Algorithm Designmentioning
confidence: 99%
“…As the highly coupled nonlinear characteristics, the actuator fault causes obvious effects on the system dynamics; therefore, they can be easily detected through monitoring abnormal system performances. Following the literature of actuator fault detection and isolation, and estimation, such fault can be considered as matched or mismatched disturbances and observed by using observers such as extended state observers (ESO) [15], [18], [19], disturbance observers (DO) [12], [20]- [22], uncertainty and disturbance estimator (UDE) [23], [24], time-delayed estimation (TDE) [25]- [27], super-twisting algorithm [28], Kalman estimators [29], unknown input observer [30], [31], etc. Then, Fault-tolerant control (FTC) that combines these observers compensation with advanced control algorithms such as active disturbance rejection control (ADRC) [32], [33], adaptive algorithms [34]- [36], or high robust gains can be employed to address the influence of the actuator fault.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed Ali et al [16] use the Super-Twisting algorithm, which is a higher-order SMC, to handle the additive and loss-ofeffectiveness actuator faults for diesel engine air path. Trinh et al [17] propose a fault estimation and fault-tolerant control strategy with two observers for a pump-controlled electrohydraulic system (PCEHS) under the presence of internal leakage faults and an external In terms of actuator FTC design for aircraft engines, there are only a few pieces of research that address the diagnosis approaches [9,10] of the actuator faults. Very few studies can be found considering the toleration/accommodation problem.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed Ali et al [16] use the Super-Twisting algorithm, which is a higher-order SMC, to handle the additive and loss-of-effectiveness actuator faults for diesel engine air path. Trinh et al [17] propose a fault estimation and fault-tolerant control strategy with two observers for a pump-controlled electro-hydraulic system (PCEHS) under the presence of internal leakage faults and an external loading force. The SMC-based FTC methods can be also connected with concepts like control allocation (CA), adaptive control, etc.…”
Section: Introductionmentioning
confidence: 99%